Does Long-Term Oxygen Therapy Reduce Exacerbations in Chronic Obstructive Pulmonary Disease? A Meta-Analysis - Rizki, Fitri Amelia; Yessy Susanty Sabri; Afriani, Afriani (HM Publisher, 2024)
Background: Chronic obstructive pulmonary disease (COPD) exacerbations contribute significantly to morbidity, mortality, and healthcare costs. While long-term oxygen therapy (LTOT) is a standard treatment for severe resting hypoxemia in COPD, its impact on exacerbations remains unclear. This meta-analysis aimed to evaluate the effect of LTOT on the frequency and severity of COPD exacerbations. Methods: A systematic search of PubMed, Embase, and Cochrane Library was conducted (January 2018 to December 2023) for randomized controlled trials (RCTs) comparing LTOT to no LTOT in COPD patients. The primary outcome was the rate of moderate to severe COPD exacerbations. Secondary outcomes included hospitalization due to exacerbations and all-cause mortality. The risk of bias was assessed using the Cochrane Risk of Bias tool. A random-effects model was used to pool data, and heterogeneity was assessed using the I² statistic. Results: Nine RCTs with 2,949 participants were included. LTOT was associated with a statistically significant reduction in the rate of moderate to severe exacerbations (Rate Ratio [RR] 0.72; 95% Confidence Interval [CI] 0.67 to 0.78; p < 0.000001), representing an estimated 28% reduction. LTOT also significantly reduced hospitalization for exacerbations (RR 0.69; 95% CI 0.61 to 0.79; p < 0.000001) and all-cause mortality (RR 0.71; 95% CI 0.57 to 0.89; p = 0.003). Conclusion: LTOT significantly reduces the frequency of moderate to severe COPD exacerbations, related hospitalizations, and all-cause mortality. These findings support LTOT use in eligible COPD patients to improve clinical outcomes.